PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN AKUNTANSI BERBASIS AKRUAL, SISTEM PENGENDALIAN INTERNAL PEMERINTAH DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN - Ternalemta, Ternalemta; Kalangi, Lintje; Tinangon, Jantje J. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to examine the effect of human resource competence, the application of accrual-based accounting, government internal control systems and the use of information technology on the quality of financial reports at the XIII / Merdeka Military Command (Kodam). This research is a quantitative study, using primary data through a questionnaire. Respondents in this study were 84 financial managers in the Kodam XIII / Merdeka work unit. The analytical method used in this research is multiple linear regression with the help of the SPSS version 23 program. The results showed that partially, the human resource competence variable, the application of accrual-based accounting, the government internal control system and the use of information technology had an effect on the quality of financial reports.